2012
DOI: 10.1097/bot.0b013e31821d700e
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Ring Injury Is Associated With Sexual Dysfunction in Women

Abstract: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
67
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 33 publications
0
67
0
1
Order By: Relevance
“…3,8 In women who have had pelvic fractures, dyspareunia, and anorgasmia are major contributors to posttraumatic sexual dysfunction. 3,4,9 In nonpelvic trauma, these sequelea are far less contributory to sexual dysfunction; however, sexual dysfunction still occurs at very high rates in the initial months after fracture treatment. The cause of sexual dysfunction in patients with nonpelvic orthopaedic trauma is likely multifactorial.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…3,8 In women who have had pelvic fractures, dyspareunia, and anorgasmia are major contributors to posttraumatic sexual dysfunction. 3,4,9 In nonpelvic trauma, these sequelea are far less contributory to sexual dysfunction; however, sexual dysfunction still occurs at very high rates in the initial months after fracture treatment. The cause of sexual dysfunction in patients with nonpelvic orthopaedic trauma is likely multifactorial.…”
Section: Discussionmentioning
confidence: 97%
“…However, within the subspecialty of orthopaedic trauma, most studies that have investigated sexual dysfunction have narrowly focused on pelvic trauma. 3,5,6,8,9 The relative inattention of orthopaedic trauma surgeons to issues related to postinjury sexual activity is likely due to limited information available on the topic and an underappreciation of the contribution of sexual dysfunction to overall functional outcomes. 16 The aim of our study was to investigate the prevalence and longitudinal improvement of patient reported sexual dysfunction after 5 common orthopaedic traumatic conditions.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…1 Recently, parathyroid hormone is believed to have both catabolic and anabolic effects on bone. 6 Vallier et al 9 conducted a prospective cohort study in a level 1 trauma center. One hundred eighty-seven women younger than 55 yr with pelvic fractures were included.…”
Section: Discussionmentioning
confidence: 99%
“…Essa hipótese foi corroborada por três dos estudos encontrados, onde mulheres com tipos diversos de fraturas pélvicas apresentaram concomitantemente disfunção sexual, seja por dor ( VALLIER, 2012), dor e disfunção do desejo sexual (CANNADA; BARR, 2010) e dor e disfunções excretoras ( WRIGHT et al, 2006). Poucos estudos relacionam diretamente as disfunções sacroilíacas com disfunções sexuais, e os que o fizeram trataram de fraturas da pelve.…”
Section: Discussionunclassified